Attributes of Organizational Culture as Predictors of Employee Burnout: A Brief Review - Zhdanova, P.R. (Sovremennaâ Zarubežnaâ Psihologiâ, 2024)
The article provides an overview of concepts related to employee burnout, organizational corporate culture, and research dedicated to studying aspects of corporate culture as predictors of employee burnout. Professional burnout, a significant issue in today's work environment, influences both the physical and mental health of employees, as well as the overall quality of their work performance. Over the past three decades, numerous studies have aimed to identify key predictors of burnout. These studies focus on aspects such as the work environment, interpersonal relationships within the team, the degree of alignment between corporate culture aspects and employees' personal values and expectations. The review of researches in this article has shown that when corporate culture does not coincide with employees' perceptions, it not only leads to reduced satisfaction levels but also contributes to the development of burnout among employees. Research underscores that aspects of corporate culture, such as the degree of social support, participation in decision-making, motivation, rewards, and the quality of relationships within the organization, can significantly impact professional stress and the emotional state of employees. Identifying attributes of corporate culture that affect employees' emotional state plays a crucial role in creating a healthy work atmosphere. В статье представлен обзор концепций эмоционального выгорания сотрудников, корпоративной культуры организации, а также исследований, которые посвящены изучению аспектов корпоративной культуры как предикторов эмоционального выгорания сотрудников. Профессиональное выгорание, которое является значительной проблемой в современной рабочей среде, оказывает влияние как на физическое, так и на психическое здоровье сотрудников, а также на общее качество их трудовой деятельности. За последние три десятилетия было проведено множество исследований, целью которых являлось выявление ключевых предикторов выгорания. Данные исследования концентрируются на таких аспектах, как рабочая среда, межличностные отношения в коллективе, степень соответствия аспектов корпоративной культуры личностным ценностям и ожиданиям работника. Обзор исследований в данной статье показал, что когда корпоративная культура не совпадает с представлениями сотрудников, это способствует не только снижению уровня удовлетворенности, но и формированию выгорания у сотрудников. Исследования подчеркивают, что такие аспекты корпоративной культуры, как степень социальной поддержки, участия в принятии решений, уровень мотивации и вознаграждения, качество взаимоотношений в организации, могут существенным образом влиять на возникновение профессионального стресса и эмоциональное состояние сотрудников. Выявление атрибутов корпоративной культуры, влияющих на эмоциональное состояние сотрудников, играет важную роль в создании здоровой рабочей атмосферы.